Tổng hợp và nghiên cứu xúc tác Cu/SBA-15 trong phản ứng oxi hóa hoàn toàn LPG - Nhân và cộng sự, Trần Văn (Vietnam Journal of Chemistry, 2014)
The mesoporous SBA-15 with lage pore sizes as a new type of material was for the first time synthesized by Stuky and Co-workers in 1998 [1]. These materials with ordered hexagonal meso structure, thick silica walls and high surface areas are obtained by using polyethylene oxide-polypropylene oxide-polyethylene oxide called P123, as structure-directing agent in acid media. The subject of this article is to obtain SBA-15 and to use Cu/SBA-15 as catalyst in the oxidation of LPG.